Efektifitas Pelatihan English Basic Conversation For Hotel Staff Terhadap Self Efficacy Karyawan Hotel Di Palembang - Leovani, Ega (Prosiding University Research Colloquium, 2018)
The research aims to investigate the effectiveness of English basic conversation for hotel staff training on the self-efficacy of hotel employees in Palembang. The background of this research is that the city of Palembang will be hosting international events such as ASIAN GAMES 2018, and the readiness of the people of Palembang in facing the MEA especially in the hotel business. Individual factors that influence self-efficacy are job involvement, organizational commitment and work environment. The data collection of this study used questionnaire method and sampling technique, that is, purposive sampling method. The selection of the intended sample is conducted because the researcher understands that the required information can be obtained from a particular group that is able to provide the desired information because they do have such information and they meet the criteria determined by the researcher. The method of analysis in this study used simple linear regression by performing the classical assumption test as a condition in performing regression test. The result of the research demonstrates that the training of English basic conversation for hotel staff has a positive and significant influence on the self-efficacy of star hotel employees in Palembang.